The Polyploid State Restricts Hepatocyte Proliferation and Liver Regeneration in Mice. Issue 3 (15th February 2019) - Wilkinson, Patrick D.; Delgado, Evan R.; Alencastro, Frances; Leek, Madeleine P.; Roy, Nairita; Weirich, Matthew P.; Stahl, Elizabeth C.; Otero, P. Anthony; Chen, Maelee I.; Brown, Whitney K.; Duncan, Andrew W.
Abstract : The liver contains a mixture of hepatocytes with diploid or polyploid (tetraploid, octaploid, etc.) nuclear content. Polyploid hepatocytes are commonly found in adult mammals, representing 90% of the entire hepatic pool in rodents. The cellular and molecular mechanisms that regulate polyploidization have been well characterized; however, it is unclear whether diploid and polyploid hepatocytes function similarly in multiple contexts. Answering this question has been challenging because proliferating hepatocytes can increase or decrease ploidy, and animal models with healthy diploid‐only livers have not been available. Mice lacking E2f7 and E2f8 in the liver (liver‐specific E2f7/E2f8 knockout; LKO) were recently reported to have a polyploidization defect, but were otherwise healthy. Herein, livers from LKO mice were rigorously characterized, demonstrating a 20‐fold increase in diploid hepatocytes and maintenance of the diploid state even after extensive proliferation. Livers from LKO mice maintained normal function, but became highly tumorigenic when challenged with tumor‐promoting stimuli, suggesting that tumors in LKO mice were driven, at least in part, by diploid hepatocytes capable of rapid proliferation. Indeed, hepatocytes from LKO mice proliferate faster and out‐compete control hepatocytes, especially in competitive repopulation studies. In addition, diploid or polyploid hepatocytes from wild‐type (WT) mice were examined to eliminate potentially confounding effects associated with E2f7/E2f8 deficiency. WT diploid cells also showed a proliferative advantage, entering and progressing through the cell cycle faster than polyploid cells, both in vitro and during liver regeneration (LR). Diploid and polyploid hepatocytes responded similarly to hepatic mitogens, indicating that proliferation kinetics are unrelated to differential response to growth stimuli. Conclusion: Diploid hepatocytes proliferate faster than polyploids, suggesting that the polyploid state functions as a growth suppressor to restrict proliferation by the majority of hepatocytes.